2016
DOI: 10.1159/000444637
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Anti-Müllerian Hormone Levels in Daughters of Women with and without Polycystic Ovary Syndrome

Abstract: Background/Aims: The aim of this study was to assess whether circulating anti-Müllerian hormone (AMH) levels in daughters of women with polycystic ovary syndrome (PCOSd) correspond with clinical and biochemical features of hyperandrogenism, polycystic ovary morphology and menstrual cycle disturbances. Methods: Menstrual cycle disturbances, hirsutism, acne and ultrasonographic ovarian morphology were assessed in 75 girls aged 13-18 years (35 PCOSd and 40 daughters of healthy women). Serum gonadotropins, androge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…15 AMH concentration is a sensitive marker of the early antral follicle number, 4 while FSH mostly reflects follicular maturation in the last 2 weeks, when follicles are gonadotropin sensitive. 16 We could not find a significant relationship between FSH and AMH and this is consistent with the study by Sir-Petermann et al, 17 while an inverse relation between AMH and serum FSH concentrations was demonstrated by Olszanecka-Glinianowicz et al 18 Anti-Müllerian hormone regulates follicle growth through the inhibition of FSH-dependent aromatase in granulosa cells. 19 As oestrogens are transformed from androgens by this aromatase, there have been studies in women with PCOS that reported negative association between AMH and oestradiol concentrations.…”
Section: Discussionsupporting
confidence: 89%
“…15 AMH concentration is a sensitive marker of the early antral follicle number, 4 while FSH mostly reflects follicular maturation in the last 2 weeks, when follicles are gonadotropin sensitive. 16 We could not find a significant relationship between FSH and AMH and this is consistent with the study by Sir-Petermann et al, 17 while an inverse relation between AMH and serum FSH concentrations was demonstrated by Olszanecka-Glinianowicz et al 18 Anti-Müllerian hormone regulates follicle growth through the inhibition of FSH-dependent aromatase in granulosa cells. 19 As oestrogens are transformed from androgens by this aromatase, there have been studies in women with PCOS that reported negative association between AMH and oestradiol concentrations.…”
Section: Discussionsupporting
confidence: 89%
“…Circulating AMH concentration has been reported as an accurate marker of the ovarian early antral follicle number, while FSH mostly reflects follicular maturation in the last 2 weeks, when follicles become gonadotropin sensitive . We did not find a relationship between FSH and AMH consistent with other studies, while one study reported an inverse relation between AMH and serum FSH concentrations . However, FSH administration did not alter AMH concentrations in women with PCOS .…”
Section: Discussionsupporting
confidence: 84%
“…Some studies show that female offspring of PCOS mothers develop symptoms of PCOS (hyperandrogenemia, cystic ovaries, abnormal menses) with adolescence and young adulthood, and some studies do not, hence whether female PCOS offspring develop PCOS themselves is controversial. For example, some studies found PCOS daughters to have increased insulin ( 50 52 ), BMI ( 53 ), ovarian volume ( 52 ), increased anti-Mullerian hormone ( 53 , 54 ), menstrual disturbances ( 54 ), and increased levels of testosterone pre- and post-pubertal ( 51 , 52 , 54 ). Meanwhile other studies found PCOS daughters to have similar BMI ( 52 , 55 ) and ovarian volume as controls ( 56 ), with no change in insulin sensitivity and glucose tolerance post-puberty ( 57 ), and no increase in testosterone in childhood ( 55 ) when compared to BMI-matched controls ( 53 , 54 ).…”
Section: Do Daughters Of Pcos Women Develop Hypertension? Data From H...mentioning
confidence: 99%